Self‐Powered Smart Textile Based on Dynamic Schottky Diode for Human‐Machine Interactions. Issue 11 (13th February 2023) - Deng, Pengfei; Wang, Yanbin; Yang, Ruizhe; He, Zijian; Tan, Yuanqiu; Chen, Zhihong; Liu, Jun; Li, Tian
Abstract: The growing demand for sustained self‐powered devices with multifunctional sensing networks is one of the main challenges for smart textiles, which are the critical elements for the future Internet of Things (IoT) and Point of Care (POC). Here, cellulose‐based smart textile is integrated with dynamic Schottky diode (DSD) to generate sustained power source (current density of 8.9 mA m⁻ 2 ) for self‐powered built‐in sensing network. In response to normal and shear motions, a pressure sensor with a sensitivity of 0.12 KPa⁻ 1 and an impact sensor are demonstrated, respectively. The woven structure of the textile contributes to signal amplification, which can also form a matrix of sensing elements for distributed sensing. The proposed strategy of fabricating self‐powered and multifunctional sensing networks with smart textiles shows tremendous potential for future intelligent society. Abstract : A self‐powered sensing network is built into primary textiles, providing an ideal platform for spatial pressure and shear motion distribution recognition. The device opens new opportunities for the development of wearable electronics in next‐generation smart textiles and future intelligent society, enabling techniques to integrate sensor systems comfortably into primary clothing, shoes, carpet, etc.